Reactive oxygen species responsive double-locked liposome collaborative photodynamic therapy for reducing electrical conduction recurrence after radiofrequency catheter ablation - Ying Zhuge; Gonghao Li; Mingyue Sun; Jiajia Zhang; Jiafeng Zou; Feng Gao; Fang Wang (International Journal of Pharmaceutics: X)
Radiofrequency catheter ablation (RFCA) is the preferred technique for the treatment of atrial fibrillation, but the recovery of electrical conduction after ablation seriously endangers the health of patients. This study aimed to develop reactive oxygen species (ROS) responsive double-locked liposome collaborative photodynamic therapy (PDT) to target the ablation area and reduce the recovery of electrical conduction after ablation. The successful synthesis of β-cyclodextrin modified with phenylboronic acid pinacol ester (OCD) was confirmed by 1H NMR and FT-IR. Furthermore, the successful synthesis of octadecylamine-modified indocyanine green (ICG-ODA) was confirmed by 1H NMR and mass spectrometry. The ICG-ODA was encapsulated in liposomes to generate a double-locked hybrid liposome (ICG-ODA@rNP), which was subsequently characterized. Several properties of ICG-ODA@rNP were evaluated, including the drug release, targeting ability and ability to inhibit electrical conduction recurrence. Moreover, a model was constructed for the blockage of electrical conduction after RFCA in rabbits to further evaluate ICG-ODA@rNP. The preliminary safety evaluation of ICG-ODA@rNP was also performed. The ICG-ODA@rNP with a uniform particle size showed excellent storage stability. The nanoparticle can sensitively release drugs under ROS environment, and exhibits excellent photothermal effects. Furthermore, ICG-ODA@rNP can circulate for a long time in vivo and accumulate significantly in the ablation area. In a pacing test with a left atrial appendage (LAA), these nanoparticles, combined with PDT, reduced the ratio of electrical conduction recovery, which was confirmed by a hematoxylin and eosin (H&E) test. Further molecular analysis revealed that ICG-ODA@rNP could increase RFCA-induced apoptosis and ROS levels. Specifically, ICG-ODA@rNP significantly increased the expression of Bax and cleaved caspase-3, and decreased the expression of Bcl-2. In addition, the excellent biosafety of the double-locked nanoparticle was verified. This study provides evidence that ICG-ODA@rNP, with the double lock characteristic and biosafety, which exhibits a targeting effect on RFCA-induced cardiac injury areas, which further reduce electrical conduction recovery in RFCA areas by collaborativing PDT.